2020
DOI: 10.1002/ctm2.214
|View full text |Cite
|
Sign up to set email alerts
|

Association of immune checkpoint inhibitor with survival in patients with cancers with protein tyrosine phosphatase receptor T mutation

Abstract: Dear Editor, We and others have shown that the tumor mutation burden (TMB) and several underlying oncogenic alterations could provide clinically predictive implications for immune checkpoint inhibitor (ICI). 1-3 Protein tyrosine phosphatases (PTPs) consist of a variety classes, and most of them are highly mutated in multiple cancers and are closely interact with innate and acquired immunity regulating immune cell activation and differentiation. 4,5 PTP receptor T (PTPRT) has been found to be the most frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Of note, PTPRT E324K, along with MAP2K1 P124L, was detected in treatment naïve sample 16 which also harbored a BRAF V600K mutation ( Figure 2 ). In melanoma, mutations in PTPRT, such as E324K, which create neoepitopes, may be associated with better outcomes for patients on immunotherapy ( 75 ). This may have been an option for this patient who subsequently had a partial response to combination BRAF/MEK inhibition with the presence of MAP2K1 P124L presumably contributing to resistance ( 76 , 77 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, PTPRT E324K, along with MAP2K1 P124L, was detected in treatment naïve sample 16 which also harbored a BRAF V600K mutation ( Figure 2 ). In melanoma, mutations in PTPRT, such as E324K, which create neoepitopes, may be associated with better outcomes for patients on immunotherapy ( 75 ). This may have been an option for this patient who subsequently had a partial response to combination BRAF/MEK inhibition with the presence of MAP2K1 P124L presumably contributing to resistance ( 76 , 77 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent two studies also revealed PTPRT mutations may be implicated in immunotherapy response. 65 , 66 He et al 65 used only one aggregated tumor cohort to explore the potential connection of PTPRT mutations and did not conduct the multivariate‐adjusted analyses, these may introduce biases to the final results. Wang et al 66 performed the relevant exploration only for NSCLC patients and lacked additional cancer type validation.…”
Section: Discussionmentioning
confidence: 99%
“…The gene may be involved in both signal transduction and cellular adhesion and is also known to inhibit malignant cell proliferation by inhibiting the STAT3 pathway [4][5][6][7]. Recent studies have reported that PTPRT mutations may be associated with the tumor mutation burden (TMB) and could provide clinically predictive implications for immune checkpoint inhibitor (ICI) therapies [8,9]. Hu et al reported that PTPRT may be involved in the early metastatic seeding of colorectal cancer [10].…”
Section: Introductionmentioning
confidence: 99%
“…To address this question, we retrospectively analyzed the somatic mutations and cancer prognostic status from the previously published data [7][8][9]. The integration of somatic mutations and clinical prognostic information from multiple cohorts retrieved 16,182 metastatic and/or stage IV cancers and 26,480 early primary cancers.…”
Section: Introductionmentioning
confidence: 99%